2008
DOI: 10.1200/jco.2007.14.2331
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Gene Expression–Defined Classes of Gastrointestinal Stromal Tumor

Abstract: CD26 appears to be a reliable biomarker of malignant GISTs of the stomach. The postoperative recurrence rate of CD26-negative cases was as low as 2.0% (two of 102). Therefore, postoperative follow-up of such patients might be made less intensive. CD26 may play an important role in the malignant progression of gastric GISTs and serve as a therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 33 publications
2
92
0
3
Order By: Relevance
“…Low expression of ING4 correlated with poor prognosis of GISTs. In addition, a recent study has identified CD26 associated with the increased risk of postoperative recurrence warrants diagnostic application, but only CD26 is associated with the outcome of the gastric GISTs [35]. In our results, tumor location has statistical significance in different ING4 expression groups.…”
Section: Discussionsupporting
confidence: 69%
“…Low expression of ING4 correlated with poor prognosis of GISTs. In addition, a recent study has identified CD26 associated with the increased risk of postoperative recurrence warrants diagnostic application, but only CD26 is associated with the outcome of the gastric GISTs [35]. In our results, tumor location has statistical significance in different ING4 expression groups.…”
Section: Discussionsupporting
confidence: 69%
“…We collected histoclinical and gene expression data of clinical GIST samples from our 2 databases 57,58 and 3 public data sets 53,59,60 from the National Center for Biotechnology Information (NCBI)/Genbank GEO and ArrayExpress databases. The 5 datasets are described in Table S5.…”
Section: Tumor Samplesmentioning
confidence: 99%
“…The 5 datasets are described in Table S5. Samples were profiled using whole-genome DNA microarrays: Affymetrix U133 Plus 2.0 [57][58][59] , and Agilent 44K. 53,60 The pooled data set contained 159 samples, including 139 with localized GIST treated with primary surgery without adjuvant imatinib.…”
Section: Tumor Samplesmentioning
confidence: 99%
“…In recent years, there has been considerable interest in applying advanced proteomics technologies to the discovery of predictive biomarkers (12,13). We and others have successfully applied MALDI MS-based protein profiling techniques for predicting the efficacy of chemoradiotherapy and molecular targeting therapy (14,15).…”
mentioning
confidence: 99%